Non-viral Causes of Liver Enzymes Elevation in Post Renal Transplant Patients - Amna Khattak; Mirza Muhammad Dawood; Zakia Rahman; Sardar Alam; Rafaqat Hussain; Muhammad Izaz; Wasia Ullah (Indus Journal of Bioscience Research, 2025)
Background: Following kidney transplantation, liver enzyme elevations (LEE) are often observed and can result from a number of causes, such as immunosuppressive medications, viral infections, and other underlying illnesses. Objectives: The aim of this study was to ascertain the incidence of LEE and identify the risk factors related to it. Patients and Methods: 200 KTRs who had received a transplant and were clear of HBV and HCV infections were included in the study. In kidney transplant recipients (KTRs) who tested negative for hepatitis B surface antigen (HBsAg) and hepatitis C virus antibodies (HCV Ab) and were free of other liver illnesses. Between December 2022 and May 2023, 200 kidney transplant patients (113 men and 87 women) participated in this observational perspective analysis. All recipients had their liver enzyme levels and other biochemical markers, such as complete blood counts, cyclosporine levels, and serum creatinine, assessed. Based on the amount of time that had passed following the transplant, the participants were split into three groups: Group I (less than three months), Group II (4–12 months), and Group III (more than a year post-transplant). Results: Incidence of LEE was greatest in male recipients (P < 0.001) and older individuals (P < 0.001). Patients who received kidneys from deceased donors were more likely to have elevated levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) than those who received kidneys from living donors (10.4% vs. 5.6% for AST and 23.8% vs. 14.8% for ALT, respectively, P < 0.001). ALT had the greatest incidence of increase among the liver enzymes, occurring in 34.3% of patients. Following transplantation, ALT and AST levels were considerably higher in the first three months and decreased in the fourth to twelve months (P < 0.001). Both univariate and linear regression studies showed a negative relationship between liver enzyme levels and renal allograft function, which grew stronger over time. Furthermore, it was shown that, although this association waned with time, cyclosporine blood levels were strongly correlated with abnormal liver enzymes. Additionally, there was a correlation between LEE and these individuals' anemia. Conclusion: In kidney transplant recipients, especially in the early post-transplant phase, liver enzyme increases are a frequent and noteworthy observation. All kidney transplant recipients should have their aminotransferases, particularly ALT, regularly and serially monitored in order to identify liver malfunction early and treat any problems.